PERTAHANAN PENCEGAHAN SERANGAN SOCIAL ENGINEERING MENGGUNAKAN TWO FACTOR AUTHENTICATION (2FA) BERBASIS SMS (SHORT MESSAGE SYSTEM) - Slamet Slamet (SPIRIT, 2022)
Advances in digital technology have made communication between humans faster and easier. On the other hand, a lot of personal information is available online through social media and services that do not have security measures in place to protect this information. Therefore, the communication system is very vulnerable and easily penetrated by intruder due to social engineering attacks. This attack aims to deceive individuals or companies by taking actions that benefit the attacker. The trick is to provide personal data such as PIN numbers, health records, and passwords. This attack phenomenon is one of the biggest challenges in maintaining the security of personal data because this attack model takes advantage of human nature which is easy to trust others. This paper provides an in-depth survey of high-success social engineering attacks, using a 2 Factor Authentication (2FA) model by examining user accounts, to detect and avoid attempted account fraud via SMS (Short Message System). Experimental results show that attack success can be reduced to 10% and aggressive intruders can be caught by 70% of users in forwarding user verification code.